Evaluating the risk of underdiagnosis of invasive breast cancer in needle biopsy-diagnosed ductal carcinoma in situ eligible for radiofrequency ablation - Hideo Shigematsu; Mutsumi Fujimoto; Kanako Suzuki; Haruka Ikejiri; Ai Amioka; Emiko Hiraoka; Shinsuke Sasada; Koji Arihiro; Morihito Okada (World Journal of Surgical Oncology)
Abstract Background Radiofrequency ablation (RFA) is considered a promising alternative to surgical excision for patients with small, unifocal early-stage breast cancer. A significant concern with the application of RFA in patients diagnosed with ductal carcinoma in situ (DCIS) via needle biopsy is the underdiagnosis of invasive cancer. The extent of this underdiagnosis in DCIS patients eligible for RFA has not been clearly defined. Methods This retrospective study assessed lesions diagnosed as DCIS via needle biopsy and eligible for RFA at our institution from April 2009 to March 2024. The eligibility criteria for RFA included a lesion size of ≤ 1.5 cm, unifocality, and clinical node negativity. Underdiagnosis was defined as the presence of invasive cancer in surgical specimens. We evaluated the frequency and risk factors associated with underdiagnosis. Results During the study period, 606 lesions were diagnosed as DCIS via needle biopsy. Of these, 209 lesions met the criteria for RFA, with underdiagnosis determined in 40 lesions (19.1%). The distribution of pathological T (pT) stages among these lesions was as follows: DCIS in 169 lesions (80.9%), pT1mi in 20 lesions (9.6%), pT1a in 5 lesions (2.4%), pT1b in 9 lesions (4.3%), pT1c in 5 lesions (2.4%), and pT2 in 1 lesion (0.5%). Multivariate logistic regression analysis identified lesion size ≥ 10 mm as a significant risk factor for underdiagnosis (p = 0.016). Adjuvant endocrine therapy and chemotherapy were administered to 26 (65.0%) and 6 (15.0%) of the underdiagnosed lesions, respectively. Conclusions Our findings highlight the risk of underdiagnosing invasive breast cancer in patients undergoing RFA for needle biopsy-diagnosed DCIS. It is crucial to acknowledge the potential for undertreatment when considering RFA as a treatment option.